2018
DOI: 10.1111/nicc.12380
|View full text |Cite
|
Sign up to set email alerts
|

Nursing workload and compliance with non‐pharmacological measures to prevent ventilator‐associated pneumonia: a multicentre study

Abstract: Most critical care nurses have good baseline knowledge of non-pharmacological measures to prevent ventilator-associated pneumonia. Failure to comply with these measures is probably more related with behavioural, structural and organizational aspects than with nursing workload. Interventions to improve compliance might be more effective if they focus on factors such as work climate and professionals' attitudes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 48 publications
2
12
0
4
Order By: Relevance
“…The compliance with preventive VAP actions in patients with low nursing workload measured by the Nursing Activites Score was lower compared to patients with higher levels of nursing workload. [34] The results of this research are in line with results verified in other studies. [30,[34][35][36] In one of these studies, carried out with 195 patients, 43 (22%) developed HAI and, as in the present study, an excessive nursing workload was identified as a risk factor for HAI (OR: 11.41; p .019).…”
Section: Discussionsupporting
confidence: 92%
“…The compliance with preventive VAP actions in patients with low nursing workload measured by the Nursing Activites Score was lower compared to patients with higher levels of nursing workload. [34] The results of this research are in line with results verified in other studies. [30,[34][35][36] In one of these studies, carried out with 195 patients, 43 (22%) developed HAI and, as in the present study, an excessive nursing workload was identified as a risk factor for HAI (OR: 11.41; p .019).…”
Section: Discussionsupporting
confidence: 92%
“…Nurses have multiple roles and central responsibility to keep patients safe in the complex healthcare environment [57,58]. The effect of personal and professional values and attitudes on the consistency of adherence to patient safety by nurses has been shown to be more important than the effect of their workloads [22]. It is believed that individual factors such as nurses' attitudes, perceptions, knowledge, and information seeking can facilitate or hinder the use of clinical practice guidelines by nurses and consequently endanger patient safety [11,26] through inconsistent adherence to patient-safety principles [59].…”
Section: Discussionmentioning
confidence: 99%
“…Institutional systemic factors influencing nurses' adherence to and compliance with patient-safety principles are as follows: the organizational patient-safety climate [21], workload, time pressure, encouragement by leaders and colleagues [22][23][24], level of ward performance [25], provision of education for the improvement of knowledge and skills [11,18], institutional procedures or protocols, and also communication between healthcare staff and patients [11]. In addition, personal motivation, resistance to change, feelings of autonomy, attitude toward innovation, and empowerment are personal factors that impact on the nurses' adherence to patient-safety principles [26].…”
Section: Introductionmentioning
confidence: 99%
“…Ventilator acquired pneumonia (VAP) is another iatrogenic disease that compromises the patient's recovery and well‐being. Jam et al () report on a cross‐sectional observational study conducted in two adult general ICUs in Spain, to examine compliance with non‐pharmacological procedure to reduce VAP. A one‐hour lecture on non‐pharmacological technique was delivered prior to the observational study and this lecture supplemented a national quality initiative to reduce VAP across Spain the year before.…”
mentioning
confidence: 99%
“…The authors conclude that knowledge of preventive measures did not guarantee compliance nor did the nurse to patient ratio. Jam et al () suggest compliance requires interventions associated with work climate and professionals' attitude and that requires a deeper understanding of the contextual factors affecting clinical practice. Indeed, such insight might illuminate beyond the statistics derived from observational schedules whether there is a gap between ‘adequate’ performance and exacting criteria to determine ‘compliance’.…”
mentioning
confidence: 99%